PENGARUH KECERDASAN EMOSIONAL DAN KEPRIBADIAN TERHADAP KINERJA KARYAWAN PADA PT BANK DANAMON INDONESIA, TBK - Sulistio, Herman; Assa, Adrie Frans; Herdiansyah, M. Izman (Manajemen Bisnis Kompetensi, 2016)
ABSTRACTEmotional intelligence in banking is needed after their intellectual, emotional intelligence deficiency can cause impaired person to use his skills. The more complex the more imÃÂportant emotional intelligence work needed. Likewise, when a young personÃ¢â¬â¢s personality traits be more apparent upon entering the elderly (Seniors) so that your youth istefined as a caricature personality of the elderly, the ederly with constructive personality tyoe will reÃÂmain employee another field or elsewhere because they get a lot of job offers even though they have retirement. In management, the organization always expect goodperformance. It should also be balance with the presence of a leader who has the dicipline governing orÃÂganization with sage and wise. Data collection tools use in this study is a questionaire that contains about emotional inteligence, personality and employee performance.Keywords: emotional quotation, personality, performance, profit